Pengaruh Iklim Komunikasi dan Motivasi Terhadap Produktifitas Kerja - Muhammad Mansyur (Akuisisi: Jurnal Akuntansi, 2020)
The purpose of this study is to perceive and rolethe influence of the communication climate and motivation to the work productivity of employees in the Center for Development and Empowerment of Educators and Business Education. This research is causality using quantitative approach with the quotation of sample is 60 personnel. Data collections used interview, observation, literature and questionnaires in the form of questions techniques. The data analysis techniques using correlation coefficients analysis, multiple regression analysis as long as variance testing using aid programme viz Microsoft Excel. These results of this research indicate that communication climate and motivation are determining factors in measuring work productivity. Optimization the level of productivity is not yet spring to the leader's range of the from their subordinates in the communication that is not running smoothly and added to the rewards received by employees that are not comparable, which causes a decrease in employee motivation.